Targeting Base Excision Repair in Cancer: NQO1-Bioactivatable Drugs Improve Tumor Selectivity and Reduce Treatment Toxicity Through Radiosensitization of Human Cancer - Starcher, Colton L.; Pay, S. Louise; Singh, Naveen; Yeh, I-Ju; Bhandare, Snehal B.; Su, Xiaolin; Huang, Xiumei; Bey, Erik A.; Motea, Edward A.; Boothman, David A. (Frontiers in Oncology, 2020)
Ionizing radiation creates lethal DNA damage and effectively kills tumor cells; however, the high dose required for a therapeutic outcome also damages healthy tissue. A method for reducing the dose without losing efficacy is highly desirable. NAD(P)H quinone oxidoreductase 1 (NQO1) is over-expressed in the majority of solid tumors in comparison with normal tissue. The ortho-naphthoquinone β-lapachone is bioactivated by NQO1, which mediates a futile redox cycle leading to DNA damage, poly (ADP-ribose) polymerase 1 (PARP1) hyperactivation, and catastrophic ATP loss, culminating in cellular lethality via NAD+-Keresis. At high in vivo doses, however, NQO1-bioactivatable drugs may induce methemoglobinemia and hemolytic anemia. Conveniently, NQO1-bioactivatable drugs synergize with PARP1 inhibitors, pyrimidine radiosensitizers, and ionizing radiation at a sub-lethal dose, allowing for a reduction in the dose of both therapeutic agents, reducing potential side effects, all the while increasing tumor specificity. Base excision repair is induced by ionizing radiation and inhibited by NQO1-bioactivatable drugs, leading to the persistence of lethal double-strand DNA breaks. In this review, we discuss the mechanisms of synergy between NQO1-bioactivatable drugs and ionizing radiation with a focus on the involvement of base excision repair. β-Lapachone and ionizing radiation combination therapy presents a unique tumor-specific, minimally toxic strategy for targeting solid tumors expressing NQO1.